2020
DOI: 10.1029/2019wr026217
|View full text |Cite
|
Sign up to set email alerts
|

Density Effects at a Concordant Bed Natural River Confluence

Abstract: Confluences are locations of complex hydrodynamic conditions within river systems. The effects on hydrodynamics and mixing of temperature-induced density differences between incoming flows are investigated at a small-size, concordant bed confluence. To evaluate density effects, results of eddy-resolving simulations for a densimetric Froude number Fr = 4.9 (weak-density-effects cases) and Fr = 1.6 (strong-density-effects cases) are compared to results of simulations in which the densities of the incoming flows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(95 citation statements)
references
References 67 publications
(186 reference statements)
5
83
0
Order By: Relevance
“…Recent work has also shown that density contrasts in which the KR is denser than the CS, as occurs for all events documented in this study, can enhance secondary flow. Modeling results indicate that this density effect becomes important when the densimetric Froude number ()Fd=U2/()g()ρ1ρ2/ρ1h1 of the flow is less than 5 (Horna ‐ (Horna‐Munoz) Munoz et al, 2020). Weak density effects related to buoyancy forces are apparent in simulations for KRCS3 (Horna Munoz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has also shown that density contrasts in which the KR is denser than the CS, as occurs for all events documented in this study, can enhance secondary flow. Modeling results indicate that this density effect becomes important when the densimetric Froude number ()Fd=U2/()g()ρ1ρ2/ρ1h1 of the flow is less than 5 (Horna ‐ (Horna‐Munoz) Munoz et al, 2020). Weak density effects related to buoyancy forces are apparent in simulations for KRCS3 (Horna Munoz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…of the flow is less than 5 (Horna -(Horna-Munoz) Munoz et al, 2020). Weak density effects related to buoyancy forces are apparent in simulations for KRCS3 (Horna Munoz et al, 2020). These effects contribute to mixing by intensifying the pattern of secondary flow associated with helical motion generated by flow curvature.…”
Section: Water Resources Researchmentioning
confidence: 97%
See 1 more Smart Citation
“…see Cheng & Constantinescu 2018, 2020; Horna-Munoz et al . 2020) have shown that buoyancy effects due unequal density differences in the incoming streams are negligible for densimetric Froude numbers larger than 10, where the densimetric Froude number is defined with the mean velocity of the flow inside the main channel, downstream of the confluence apex, the mean flow depth inside the main channel and the relative density difference between the two streams. The present work is directly relevant for cases with negligible buoyancy effects where the mixing interface resembles a shallow mixing layer and a lateral lock-exchange flow does not develop downstream of the confluence apex.…”
Section: Introductionmentioning
confidence: 99%
“…However, their findings were not systematically used to evaluate existing analytical transverse mixing solutions (as done by Rathbun & Rostad, 2004, and earlier works by Yotsukura, Beltaos, and others in the 1970s to 1980s), let alone to develop and improve them. On the other hand, high‐resolution numerical studies using computational fluid dynamics simulations (e.g., Cheng & Constantinescu, 2018; Constantinescu et al, 2016; Horna Munoz et al, 2020; Lyubimova et al, 2014; Shakibainia et al, 2010) have brought detailed insight on mixing processes downstream of confluences but their computational cost is still too high for engineering applications to large river domains.…”
Section: Introductionmentioning
confidence: 99%